Occurrence and diversity of arbuscular mycorrhizal fungi in trap cultures from El Palmar National Park soils - Velázquez, María Silvana (2011)
The objective of this study was to assess and compare the diversity of arbuscular-mycorrhizal fungi (AMF) obtained from five vegetation types—gallery forest, grassland, marsh, palm forest, and scrubland—within El Palmar National Park (Entre Ríos province, Argentina) through trap cultures with soil as the source of inoculum. Three different plant species—Lolium perenne L., Plantago lanceolata L., and Trifolium pratense L.—were used as trap plants. The experiment, conducted for two years under glasshouse conditions, showed that spore number increased during the second year in all the trap cultures from the five vegetation types, with Glomeraceae being most abundant in the last year. A total of 34 morphospecies were identified at the species level (32 morphospecies during the first year and 26 during the second). The species richness and biodiversity index decreased in the second year and were significantly different between the marsh and the palm forest. The soil-based trap culture isolation procedure indicated the presence of Glomeromycota species not registered from field samples: three belonging to the Acaulospora genus, one to the Glomus genus, and three to the Gigaspora genus. The results of this study confirmed the local competiton of Glomeraceae against other Glomeromycota families under glasshouse conditions.